Sensitivity Analysis of Flash Flood Hazard on Sediment Load Characteristics - Liu, Hongxi; Yi, Yujun; Jin, Zhongwu (Frontiers in Earth Science, 2021)
Ongoing changing climate has raised the attention towards weather driven natural hazards, such as rain-induced flash floods. Flooding model provides an efficient tool in flash flood warning and hazard management. More and more evidence showed significant impacts from sediment on hydrodynamic and flooding hazard of flash flood. But little information is provided regarding flooding hazard sensitivity to sediment characteristics, which hampers the inclusion of sediment characteristics into flash flood warning system and hazard management. This study used 1D model to simulate flood hazards. After calibrating and validating the hydrodynamic model, we carried out simulations to test the sensitivity of flood hazard to sediment characteristics of inflow point, size distribution and concentration. Our results showed that sediment from highly erosive slopes affects the flooding hazard more than sedimentsfrom watershed. This is particularly true when sediments are fine particles with medium size of 0.06 mm. When medium particle size of sediments increased over 1 mm, most of sediment is deposited in the river and we see little affect on flooding hazard downstream. Sediment concentration significantly influenced the flooding hazard, but was less important compared to sediment inflow point and medium particle size. Our study suggested to consider more characteristics than concentration when including sediments into flash flood warning system.